Disiplin Protokol Kesehatan Di Badan Pembinaan Hukum Nasional - Anisah, Anisah; Shalahuddin, Shalahuddin (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2023)
The application of health protocol discipline plays an important role for employees of the Badan Pembinaan Hukum Nasional (BPHN). The purpose of this study was to determine the application of the discipline of employee health protocols in the era of new habits. This research was conducted using primary data types in the form of interviews and secondary data obtained through journals. The method used is descriptive qualitative. Data collection techniques in this study were through observation, interviews and supporting documents for the application of health protocol disciplines. The results showed that the implementation of the 3M health protocol discipline at the Badan Pembinaan Hukum Nasional had not been implemented by employees properly. There are still many employees who neglect to implement health protocols such as frequently removing masks, not maintaining distance and not maintaining hand hygiene. This happened because there was no special team that supervised the implementation of the health protocol discipline which is usually called the Covid-19 Task Force, thus making employees undisciplined in applying the health protocol. In order for employees to be more disciplined in health protocols, there is a proposal for BPHN, namely by forming a Covid-19 Task Force team by making a description that clearly contains the duties and functions of the Covid-19 Task Force as well as making a form for written sanctions and a form for evaluating the implementation of health protocol discipline. A description of the duties and functions of the Covid-19 Task Force and the form have been made.